The efficacy of the FIFA 11+ program in the collegiate male soccer player (USA) - Silvers, H.; Mandelbaum, B.; Bizzini, M.; Dvorak, J. (British Journal of Sports Medicine, 2014)
Background: The efficacy of the FIFA 11+ program in collegiate soccer. Objective: Can the FIFA 11+ effectively reduce injury in the competitive male soccer player? Design: Prospective randomized controlled trial conducted in the NCAA. Every institution (N=411) was contacted via a formal letter, email and phone call. Sixty-one institutions consented to participate. Human ethics approval was acquired through Quorum IRB, Seattle, WA, USA. The intervention group received an instructional DVD, manual and placards. A injury surveillance database was utilized (HealtheAthleteTM, Kansas) for data collection. Every exposure, injury, and compliance data was entered weekly. Setting: NCAA institutions playing competitive soccer. Participants: 61 institutions completed the study: 34 control (N=850 athletes) and 27 intervention (N=675 athletes). Intervention: The FIFA 11+ injury prevention program served as the intervention program. It was utilized three times per week for the duration of the season. Main outcome measurements: Specific injuries, athletic exposures, program compliance and time loss were recorded. Results: In the intervention Group (IG), 285 injuries were reported (mean=10.56 injuries/team+/- 3.64) compared to 665 injuries (mean=20.15 +/- 11.01) in the control group (CG). The number of athletic exposures was 35,226 (Games: 10 935 AE, Practice: 24 291AE) for the IG and 44 212 (Games: 13 624 AE, Practice: 30 588 AE) in the CG). The incidence rate (IR) was 8.09/1000 AE (95% CI) in the IG compared to 15.04/1000 AE (95% CI) in the CG (P=.00117). Total days missed due to injury was 2 824 (mean=9.94) in the IG compared to 8776 days (mean=13.20) in the CG. Conclusions: The FIFA 11+ was shown to reduce injury rates and time loss in the male collegiate soccer player in a statistically significant manner.